CECILIA Regional Climate Simulations for Future Climate: Analysis of Climate Change Signal - Michal Belda; Petr Skalák; Aleš Farda; Tomáš Halenka; Michel Déqué; Gabriella Csima; Judit Bartholy; Csaba Torma; Constanta Boroneant; Mihaela Caian; Valery Spiridonov (Advances in Meteorology)
Regional climate models (RCMs) are important tools used for downscaling climate simulations from global scale models. In project CECILIA, two RCMs were used to provide climate change information for regions of Central and Eastern Europe. Models RegCM and ALADIN-Climate were employed in downscaling global simulations from ECHAM5 and ARPEGE-CLIMAT under IPCC A1B emission scenario in periods 2021–2050 and 2071–2100. Climate change signal present in these simulations is consistent with respective driving data, showing similar large-scale features: warming between 0 and 3°C in the first period and 2 and 5°C in the second period with the least warming in northwestern part of the domain increasing in the southeastern direction and small precipitation changes within range of +1 to −1 mm/day. Regional features are amplified by the RCMs, more so in case of the ALADIN family of models.